Monitoring and evaluation the implementation the strategy anh policy on science, technology and innovation in some countries in the world - Nguyen Lan Anh; Bui Ngoc Thu Ha (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Monitoring and evaluation the implementation of science, technology and innovation strategy and policy is an important task, which contributing to ensuring that the implementation of programs, projects, policy and strategy is implemented effectively and sustainably. The monitoring and evaluation framework is a tool designed to guide the implementation of monitoring and evaluation functions during the implementation of strategy and policy in order to improve the effectiveness of the implementation of strategies and policies in practice, meeting defined objectives. This article reviews experiences in monitoring and evaluating the implementation of science, technology and innovation strategy and policy in some countries, thereby suggesting some lessons learned for Vietnam. Code: 23120401